Pedagogy of Compassion: Implementing a Love-Based Arabic Curriculum in Islamic Elementary Schools - Nurul Hidayah; Mukmin Mukmin; Sakina Fitri; Febri Yansyah; Daud Elega (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
Educational transformation requires curriculum to function not merely as an administrative framework but also as a pedagogical instrument for character formation. However, Arabic language learning in Islamic elementary schools remains predominantly teacher-centered, often creating psychological distance between students and the target language. This study aims to explore the implementation of a Love Based Curriculum as a humanistic pedagogical practice in Arabic language learning. Employing a qualitative approach with an intrinsic case study design, data were collected through observations, interviews, document analysis and analyzed using thematic analysis. The Love-Based Curriculum has evolved beyond normative character education into a humanistic pedagogical practice integrating academic, emotional, social, and spiritual dimensions. This was reflected in four interconnected dimensions: humanistic instructional planning through the integration of Pancacinta values, compassionate classroom practices fostering supportive teacher student relationships, humanistic assessment emphasizing students’ participation and socio-emotional development, and the rehumanization of Arabic learning through emotionally safe and engaging classroom experiences. Nevertheless, implementation remained constrained by learner diversity, linguistic difficulties, teacher dependency, and limited systematic assessment of affective development.